Cultural Practices of Place
XIV, 258 p. 13 illus., 7 illus. in color.
Keywords: The notion of sense of place developed across disciplines to study the range of experiential, relational, and emotive attachments between people and spatial constellations. This collection proposes a sense of placing to render visible complex cultural practices of meaning making in, around, and through place, while also encouraging reflection on the epistemes of position. Whether as physical location, social orientation, or facet of differentiation, relations of place are a central consideration of Cultural Studies: yet, this has not been afforded sustained engagement as a means to analyse dynamics of cultural power. Unpicking the practices that determine, while being determined by, the heres, theres, and somewheres in-between, the contributions showcase engagement with diverse media through which senses are placed and places are sensed. Gathering perspectives from sociology, law, philosophy, human geography, literature, and cultural studies, the volume is an interdisciplinary endeavour to practice a dialogic placing across often siloed academic work. Sarah Earnshaw (she/her) is a postdoc in American and Cultural Studies whose research interests revolve around spatial compositions of class struggle, labour mobilisation, and practices of freedom and autonomy. She has recently published in Lateral (2024) as well as the monograph Human Rights and Sovereign Standards in US Security (2025).